Assessment of the Effectiveness of Community Health Promoters in Hypertension Care in Imenti North Sub-County, Kenya - Vincent Mukundi Gitonga; Ananias Njagi Nkonge; Elias Kinoti; Patrick Kubai (Asian Journal of Medicine and Health, 2026)
Background: Hypertension remains an important public health challenge in Imenti North Sub-County, Meru County, Kenya, where Community Health Promoters (CHPs) support community-based screening, monitoring, education, and treatment adherence. Aim: This study assessed the effectiveness of CHPs in hypertension care by examining blood-pressure monitoring resources, adherence support, and barriers to service delivery. Methods: A descriptive cross-sectional survey was conducted among 208 CHPs selected by simple random sampling from 450 CHPs across 45 community units. Data were collected using a structured questionnaire and analyzed in SPSS using descriptive and inferential statistics. Results: Almost all CHPs had received initial hypertension-care training (99.0%), and 91.8% had access to functional blood-pressure machines. Weekly machine use was reported by 66.4%. Medication adherence counselling was provided by 96.6% of CHPs, while 89.4% used home visits as the primary follow-up method. Patient-reported improvement in medication adherence was reported by 97.1% of CHPs. However, only 48.1% had received refresher training, 54.8% identified lack of refresher training as the leading training challenge, and 66.8% experienced battery stock-outs lasting more than one day. Batteries were cited as the dominant resource barrier by 94.7%. Refresher training and resource availability were significantly associated with reported care outcomes. Conclusion: The findings indicate an important role for CHPs in community-based hypertension care in Imenti North Sub-County. Regular refresher training, reliable supplies, and attention to workload and mobility barriers may strengthen the consistency and quality of care.